English Listening Lesson Library Online (ELLLO) as a Supporting Media in Learning Listening - Sukmawati Tono Palangngan; Haryanto Atmowardoyo; Sukardi Weda (Universitas Negeri Makassar, 2016)
This research aims to find out: (1) whether the use of English Listening Lesson Library Online (ELLLO) affects the students’ Listening comprehension achievement and (2) students’ perception tow Engish Listening Lesson Library Online (ELLLLO). This research employed Quan-Qual method with a type of quasi-experimental design namely regression discontinuity design. The population was the second year students of SMAN 3 Palopo which consisting of nine classes in 2014/2015 academic year. The total number of population was 270 students. This research used the combination of random sampling and nonrandom sampling technique, random sampling to decide the sample of the quantitative analysis and nonrandom sampling to decide the qualitative analysis. The data were collected by two instruments namely a listening test and interview. The description of data collected through the listening comprehension test showed that ELLLO (English Listening Lesson Library Online) is significantly affecting the students listening comprehension. All students agree that English listening Lesson Library Online (ELLLO) is a good supporting media since they have used it for about six weeks and their favourite activity is game activities. Keywords: effect, ELLLO, listening